Blood‐based detection of lung cancer using cysteine‐rich angiogenic inducer 61 (CYR61) as a circulating protein biomarker: a pilot study. Issue 11 (3rd October 2021) - Ac\̌kar, Lucija; Casjens, Swaantje; Andreas, Antje; Raiko, Irina; Brüning, Thomas; Geffken, Maria; Peine, Sven; Kollmeier, Jens; Johnen, Georg; Bartkowiak, Kai; Weber, Daniel Gilbert; Pantel, Klaus
Abstract : Lung cancer is the most often diagnosed cancer and the main cause of cancer deaths in the world compared with other tumor entities. To date, the only screening method for high‐risk lung cancer patients is low‐dosed computed tomography which still suffers from high false‐positive rates and overdiagnosis. Therefore, there is an obvious need to identify biomarkers for the detection of lung cancer that could be used to guide the use of low‐dosed computed tomography or other imaging procedures. We aimed to assess the performance of the protein cysteine‐rich angiogenic inducer 61 (CYR61) as a circulating biomarker for the detection of lung cancer. CYR61 concentrations in plasma were significantly elevated in 87 lung cancer patients (13.7 ± 18.6 ng·mL −1 ) compared with 150 healthy controls (0.29 ± 0.22 ng·mL −1 ). Subset analysis stratified by sex revealed increased CYR61 concentrations for adenocarcinoma and squamous cell carcinoma in men compared with women. For male lung cancer patients versus male healthy controls, the sensitivity was 84% at a specificity of 100%, whereas for females, the sensitivity was 27% at a specificity of 99%. The determination of circulating CYR61 protein in plasma might improve the detection of lung cancer in men. The findings of this pilot study support further verification of CYR61 as a biomarker for lung cancer detection in men. Additionally, CYR61 is significantly elevated in women but sensitivity and specificity for CYR61 are too low for the improvement of the detection of lung cancer in women. Abstract : In this study, we assessed the performance of circulating CYR61 concentration as a biomarker in plasma of patients with lung cancer (LC) by ELISA. Subset analysis stratified by sex revealed increased CYR61 concentrations for adenocarcinoma and squamous cell carcinoma in men compared with women. Our data support the further verification of CYR61 as a biomarker for lung cancer detection in men. Additionally, CYR61 was significantly elevated in women, but sensitivity and specificity for CYR61 were too low for improvement of LC detection.